Regional Integration at the Forefront of Mozambique’s Energy Success - Hundermark, Charnè (cnbcafrica, 2021)
As one of leading resource-rich countries in sub-Saharan Africa, Mozambique has the potential to not only significantly advance its own socioeconomic status, but also dramatically boost economic growth throughout the region. According to the World Bank Group, regional integration helps countries to overcome divisions that impede the flow of goods, services, capital, people and ideas. As large-scale energy projects are expected to come online in Mozambique through 2023, the country has observed renewed political commitment to establishing sustainable regional integration with neighboring governments and private operators.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; L - english / inglês; economic development / desenvolvimento económico

Actualidade Económica de Moçambique: Preparação para Recuperação (World Bank Group, 2021)
The global pandemic has taken a heavy toll on Mozambique’s economy. In 2020, the country experienced its first economic contraction in nearly three decades. COVID-19 (coronavirus) hit the economy as it was attempting to recover from the slowdown triggered by the hidden debt crisis and the tropical cyclones in 2019. Real gross domestic product (GDP) contracted by 1.3 percent in 2020, compared to a pre-Covid estimate of 4.3 percent, as external demand declined, domestic lockdown measures disrupted supply chains and depressed domestic demand, and liquified natural gas (LNG) investments were delayed. COVID-19 has caused a sudden income loss for enterprises and households, worsening living conditions, especially for the urban poor largely engaged in the informal sector. According to the National Institute of Statistics, as of June 2020, about 120,000 jobs were lost and 63,000 employment contracts suspended, with women being the most affected. Around 3 percent of the firms affected were forced to cease their activity. Services activities are the hardest hit. The tourism and hospitality industries have particularly suffered a steep decline in revenues. COVID-19 has jeopardized years of hard-won development gains, with about one million people estimated to have slipped into poverty in 2020 (as measured by the international poverty line of 1.90 US Dollars per day). While there is great uncertainty about the path of the pandemic, the economy is expected to gradually recover from 2021 as aggregate demand rebounds and LNG investments and extractive production gain momentum. Despite the expected recovery, the widespread deployment of COVID-19 vaccines will be at the core of a resilient recovery. This Economic Update explores the implications of COVID-19 for the economy, businesses and households. It makes recommendations for moving forward—in the short-term relief phase, as well as over the medium and longer term in order to 'build back better~!!.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde; private sector / setor privado

Mozambique Economic Update : Setting the Stage for Recovery (World Bank Group, 2021)
The global pandemic has taken a heavy toll on Mozambique’s economy. In 2020, the country experienced its first economic contraction in nearly three decades. COVID-19 (coronavirus) hit the economy as it was attempting to recover from the slowdown triggered by the hidden debt crisis and the tropical cyclones in 2019. Real gross domestic product (GDP) contracted by 1.3 percent in 2020, compared to a pre-Covid estimate of 4.3 percent, as external demand declined, domestic lockdown measures disrupted supply chains and depressed domestic demand, and liquified natural gas (LNG) investments were delayed. COVID-19 has caused a sudden income loss for enterprises and households, worsening living conditions, especially for the urban poor largely engaged in the informal sector. According to the National Institute of Statistics, as of June 2020, about 120,000 jobs were lost and 63,000 employment contracts suspended, with women being the most affected. Around 3 percent of the firms affected were forced to cease their activity. Services activities are the hardest hit. The tourism and hospitality industries have particularly suffered a steep decline in revenues. COVID-19 has jeopardized years of hard-won development gains, with about one million people estimated to have slipped into poverty in 2020 (as measured by the international poverty line of 1.90 US Dollars per day). While there is great uncertainty about the path of the pandemic, the economy is expected to gradually recover from 2021 as aggregate demand rebounds and LNG investments and extractive production gain momentum. Despite the expected recovery, the widespread deployment of COVID-19 vaccines will be at the core of a resilient recovery. This Economic Update explores the implications of COVID-19 for the economy, businesses and households. It makes recommendations for moving forward—in the short-term relief phase, as well as over the medium and longer term in order to 'build back better~!!.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde; private sector / setor privado

Desafios para Moçambique - 2021 - Macuane, José Jaime; Siúta, Moisés (Instituto de Estudos Sociais e Económicos, 2021)
PARTE I – POLÍTICA Navegando o espaço cívico em contexto da pandemia da Covid-19: O caso de Moçambique / Crescêncio Pereira, Salvador Forquilha e Alex Shankland A Covid-19 e as vacinas em Moçambique: Algumas notas para reflexão a partir da teoria “sociedade de risco” / Lúcio Posse A Covid-19 e suas implicações na governação municipal em Moçambique: Um estudo de caso a partir do município de Gondola / Bernardino António PARTE II – ECONOMIA Política económica em contexto de pandemia: Uma reflexão em torno das medidas de mitigação dos efeitos da Covid-19 sobre a economia de Moçambique / Carlos Muianga e Yasfir Ibraimo A recessão económica em Moçambique: Foi a Covid-19? – Um olhar a partir do sector externo / Michael Sambo Essencial para quê? Uma visão global de reprodução social sobre a reorganização do trabalho durante a pandemia da Covid-19 / Sara Stevano, Rosimina Ali e Merle Jamieson PARTE III – SOCIEDADE “Se alguém está cansado de viver”: A economia informal, o estado e a segurança social / Ruth Castel-Branco Acção social em contexto da Covid-19: Respostas e desafios em Moçambique / Moisés Siúta e Félix Matusse Lições da Covid-19 sobre o papel da poupança doméstica: O que dizer de Moçambique? / Moisés Siúta PARTE IV – MOÇAMBIQUE NO MUNDO Globalização económica e desafios de desenvolvimento humano em contexto de crise em Moçambique / Salim Cripton Valá Alargamento de espaço para o diálogo de políticas Sul-Sul: Aprender com as iniciativas lideradas pela sociedade civil / Lídia Cabral, Les Levidow e Claudia Job Schmitt
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

Política económica em contexto de pandemia: uma reflexão em trono das medidas de mitigação dos efeitos da COVID-19 sobre a economia de Moçambique - Muianga, Carlos; Ibraimo, Yasfir (Desafios para Moçambique 2021, 2021)
Este artigo pretende reflectir sobre as medidas para mitigação dos efeitos da COVID-19 na economia de Moçambique e as suas implicações analíticas. Diferentemente de estudos anteriores sobre os impactos da pandemia e das medidas de mitigação adoptadas pelo Governo de Moçambique (Mapisse et al., 2021), este artigo parte da análise da estrutura da economia e do seu padrão de acumulação nas últimas duas décadas, na tentativa de melhor questionar a eficácia destas medidas. O artigo argumenta que, à semelhança das crises cíclicas pelas quais a economia de Moçambique passou nas últimas décadas (Castel-Branco and Ossemane, 2010; Castel-Branco, 2017), a crise provocada pela COVID-19 expõe e exacerba as fragilidades e vulnerabilidades do padrão de crescimento e a sua limitada capacidade em resolver questões centrais de transformação social e económica. Dadas as fragilidades e vulnerabilidades associadas ao padrão de crescimento económico e ao «modelo» de política económica, as medidas de mitigação dos efeitos da pandemia sobre a economia são limitadas relativamente à complexidade dos impactos socioeconómicos da COVID-19. Mais do que a sua limitada capacidade para relançar a actividade produtiva, dada a estrutura da economia, as mesmas são insuficientes para lidar com os impactos mais severos da pandemia, sobretudo para os grupos sociais mais vulneráveis. Entretanto, a COVID-19 tem chamado a atenção à necessidade de acção política e mudança «radical» na prossecução da política económica, incluindo o papel do Estado na economia (Stevano et al., 2021). Contudo, as principais medidas de política económica até então adoptadas continuam a seguir um «modelo» que, há décadas, se tem mostrado ineficaz em resolver, a médio e longo prazo, as questões de transformação económica e social do País. Este artigo está organizado em quatro secções, incluindo a introdução. A segunda faz uma breve descrição e análise da estrutura da economia e do padrão de crescimento económico em Moçambique, nas últimas duas décadas. O objectivo desta secção é fornecer uma base analítica que ajude a interrogar as medidas de mitigação dos efeitos da COVID-19 sobre a economia, enquanto, ao mesmo tempo, ajuda a explicar o tipo de economia que a pandemia encontrou, as suas características fundamentais e o seu funcionamento. A terceira secção descreve as principais medidas adoptadas pelo BM e pelo Governo para mitigar os efeitos da COVID-19, questionando-as em função da estrutura da economia e do quadro de implementação de política monetária e fiscal e as suas contradições e tensões. A quarta secção conclui e avança algumas questões para reflexão.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; government policy / politica governamental; health - COVID-19 / saúde – COVID-19

A recessão económica em Moçambique: foi a COVID-19? Um olhar a partir do sector externo - Sambo, Michael Godet (Desafios para Moçambique 2021, 2021)
Este artigo argumenta que a crise económica em Moçambique não resulta da eclosão da pandemia em si, e dos seus efeitos directos na economia moçambicana, mas sim, que a pandemia exacerbou uma crise pré-existente. O artigo resulta de análise bibliográfica e documental, com ênfase para a análise de dados estatísticos de múltiplas fontes internacionais e nacionais, destacando as fontes oficiais, e analisa as dinâmicas económicas no contexto da COVID-19, com enfoque nas relações económicas de Moçambique com o resto do Mundo desde antes da eclosão da pandemia até aos princípios de 2021. Além da introdução, este artigo é desenvolvido em duas secções seguidas da conclusão. A primeira secção analisa as dinâmicas das políticas públicas no contexto da dependência externa, e a segunda investiga as dinâmicas da economia de Moçambique em relação ao resto do mundo, analisando os antecedentes e as variações no âmbito da COVID-19, com vista a aferir a sua relação; segue-se finalmente uma conclusão e implicações da análise.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19